Significance of Heat Treatment in Reduction of Antibiotic Residues from Livestock Food Products - Pame, Kuleswan; Laskar, S.K. (Current Perspectives in Agriculture and Food Science Vol. 9, 2024)
The primary objective of every country is to guarantee the availability of safe food resources for its consumers. However, more recently increase in the occurrences of antibiotic drug residues in livestock products has posed a major public health issue around the globe particularly in developing countries. The use of antibiotic drugs in livestock production cannot be avoided. It is being used as a therapeutic, prophylactic and even as growth promoters. However, the irrational use of antibiotics in livestock has led to the accumulation of its residues in animal tissues and their products. The deposition of residues in food originating from livestock animals is a critical problem in many countries and the problem is more serious in developing countries around the world, due to their potential health hazards. Generally, the residues are more procedurally estimated on uncooked meat, but meat food undergoes a varying degree of heat treatment during the cooking process, therefore information on the heat stability of antibiotics is an important area of research to give a more accurate estimate of consumer’s exposure to these antibiotic compounds and their metabolites. The reduction of antibiotic residues in meat and meat products is influenced by the dual effect of time and temperature during heat treatment. Cooking methods cannot totally eliminate antibiotic residues from food, but they can possibly decrease the concentration of residues. Therefore to enhance food safety, drug withdrawal periods should be strictly followed and residue limits should be strictly enforced, at the same time use of drugs with shorter withdrawal periods should be encouraged.